PENGARUH MEKANISME CORPORATE GOVERNANCE, UKURAN KANTOR AKUNTAN PUBLIK, DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS LAPORAN KEUANGAN (Media Riset Akuntansi, 2022)
This study aimed to analyze the effect of size of independent commissioners, the size of the audit committee, public accounting firm size, and independent auditors on the quality of financial statements in manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017. This study uses four independent variables, such a size of independent commissioners, the size of the audit committee, public accounting firm size, and independent auditors. Meanwhile, the dependent variable of this study is the quality of the financial report. This research use secondary data with a purposive sampling method. The sample used is 40 manufacturing companies and bringing the total sample of this study is 45 samples. Analysis instrument has been done by using multiple linear regressions analysis. Based on the results of research, it is known that the public accounting firm size and independent auditors on the quality of financial statements, the size of independent commissioners and the size of the audit committee is not related to the quality of financial statements.